2020
DOI: 10.1097/mnm.0000000000001315
|View full text |Cite
|
Sign up to set email alerts
|

Dosimetry-guided radioiodine therapy of hyperthyroidism: long-term experience and implications for guidelines

Abstract: Background Long-term follow-up after radioactive iodine therapy (RIT) for Graves’ disease and toxic thyroid autonomy is incompletely addressed by current guidelines. We retrospectively analyzed the clinical course of 1233 out of 1728 consecutive Graves’ disease (n = 536) and thyroid autonomy (n = 1192) patients after dosimetry-guided RIT to optimize follow-up. Methods Patients were referred between 1990 and 2018; follow-up was monitored according to ava… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(4 citation statements)
references
References 41 publications
0
4
0
Order By: Relevance
“…The NIS expression at the PM of thyroid follicular cells is not only important for thyroid hormone biosynthesis but also constitutes the cornerstone for radioiodine (RAI) therapy for differentiated thyroid cancer (DTC) [4][5][6]. Indeed, the selective use of RAI, based on patients' individual risk, is often recommended as an adjuvant treatment for DTC, for which the standard care includes total thyroidectomy and TSH-suppressive therapy.…”
Section: Introductionmentioning
confidence: 99%
“…The NIS expression at the PM of thyroid follicular cells is not only important for thyroid hormone biosynthesis but also constitutes the cornerstone for radioiodine (RAI) therapy for differentiated thyroid cancer (DTC) [4][5][6]. Indeed, the selective use of RAI, based on patients' individual risk, is often recommended as an adjuvant treatment for DTC, for which the standard care includes total thyroidectomy and TSH-suppressive therapy.…”
Section: Introductionmentioning
confidence: 99%
“…Few studies compared efficacy and safety between these methods in this indication. Only one randomized study in patients with autonomous nodules showed equivalent efficacy with lower risk of hypothyroidism for calculated than fixed radioactivity methods [26], [28], [29], [30]. However, although more complex to implement, dosimetric methods should ideally be preferred, as internal vectored radiotherapy should be performed with "the lowest effective activity possible" (ALARA principle: As Low As Reasonably Achievable).…”
Section: Radioactive Iodine Therapy For Autonomous Thyroid Nodulesmentioning
confidence: 99%
“…The speed of regression of hyperthyroidism depends on factors influencing iodine uptake, and correlates with radioactivity level [29]. The risk of secondary hypothyroidism persists for up to 20 years after RAI therapy, with cumulative rates of approximately 7% at 6 months to 30% at 20 years [28], [32]. The risk of hypothyroidism correlates with patient age, radioactivity level, TSH value at the time of therapy, and pre-existing underlying thyroid disease (presence of antithyroid antibodies before RAI therapy) [27], [28], [31].…”
Section: Radioactive Iodine Therapy For Autonomous Thyroid Nodulesmentioning
confidence: 99%
See 1 more Smart Citation